Children's well-being in contexts of poverty: approaches to research, monitoring and participation - Camfield, L; Streuli, N; Woodhead, M (2008)
Monitoring, protecting and promoting ‘well-being’ are central to realisation of children’s rights. Yet definitions of the concept are both variable and can appear conceptually confused. Competing research paradigms engage with the concept and its measurement, while applications of well-being in policy are equally contested. This paper outlines some of the major debates, as a starting point for reviewing three contrasting approaches to well-being: indicator-based, participatory and longitudinal research. In particular, it focuses on applications of the concept in contexts of child poverty worldwide. We suggest there are some promising signs of integration amongst these approaches, and argue that well-being does have potential as a bridging concept, at the same time highlighting inequalities, acknowledging diversities, and respecting children’s agency. Drawing on the experience of Young Lives, a 15-year, four-country longitudinal study of child poverty, we suggest that methods for studying child well-being in global contexts should be dynamic and sensitive to culture and time, as well as to the trade-offs that children are required to make between themselves and others. We argue that dynamic approaches are especially important in research with children as they address how people change in time. Well-being is understood by Young Lives to be about real people and the social contexts they inhabit. It can act as a lens - similar to culture - which recognises that outcomes of deprivation are influenced by children and their responses to and interpretation of events. Accessing children’s views in the context of their communities is important and can increase the accuracy and credibility of research data.